(3GdJfhjQ aj ESbGW GdJOHjQs - (3CMeO Hf eMeO Hf YHO GdcQje Hf YWGA Gddg GdScfOQj, GHf YWGA Gddg , JGL GdOjf CHh GdaVd,J (B709 (3g` s ((3UYOI s)
(3ChdgG (B:s
(3GdMeO ddg GdeJaQO HGdNdb hGdJOHjQ CeG HYO , EYde jG CNj Cf ef WdH GdhUhd Edi Gddg aMbjb Ydjg CdG jCJi GdCejQ ZdG ef HGHg s
(3BNQgG (B:s
(3hGNJe dfG efc HNjQ jG QH GdYGdejf hGdMeO ddg QH GdYGdejf Je hced s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B142s
(3YdjgG JedcGJ cKjQI CbOegG Jedc ai BNQgG eVHH Ydjg hgh HJGQjN (B970(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B121s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs